2014
DOI: 10.1007/s10295-013-1371-6
|View full text |Cite
|
Sign up to set email alerts
|

DyP-type peroxidases: a promising and versatile class of enzymes

Abstract: DyP peroxidases comprise a novel superfamily of heme-containing peroxidases, which is unrelated to the superfamilies of plant and animal peroxidases. These enzymes have so far been identified in the genomes of fungi, bacteria, as well as archaea, although their physiological function is still unclear. DyPs are bifunctional enzymes displaying not only oxidative activity but also hydrolytic activity. Moreover, these enzymes are able to oxidize a variety of organic compounds of which some are poorly converted by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
201
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(212 citation statements)
references
References 49 publications
1
201
0
3
Order By: Relevance
“…Additionally, DyP-type peroxidase also increased at 28°C in this species and subsequently decreased at 32°C in M. trossulus, possibly indicating a lower antioxidant capacity with exposure to this temperature. DyP-type peroxidases represent a novel family of heme-containing peroxidases whose function has yet to be determined (Colpa et al, 2014), although it is possible that they play a role in decreasing peroxynitrite (Trujillo et al, 2008). Thus, M. trossulus was unable to activate an antioxidant response at the highest temperature, a limitation likely contributing to its lower thermal tolerance.…”
Section: Temperature-induced Antioxidant Responsesmentioning
confidence: 99%
“…Additionally, DyP-type peroxidase also increased at 28°C in this species and subsequently decreased at 32°C in M. trossulus, possibly indicating a lower antioxidant capacity with exposure to this temperature. DyP-type peroxidases represent a novel family of heme-containing peroxidases whose function has yet to be determined (Colpa et al, 2014), although it is possible that they play a role in decreasing peroxynitrite (Trujillo et al, 2008). Thus, M. trossulus was unable to activate an antioxidant response at the highest temperature, a limitation likely contributing to its lower thermal tolerance.…”
Section: Temperature-induced Antioxidant Responsesmentioning
confidence: 99%
“…Although the first DyP-type peroxidase was isolated from fungi, subsequent genome sequence analysis has revealed that this superfamily of enzymes is also prominent in bacteria. 13 DyP-type peroxidases typically require hydrogen peroxide to form the oxo-ferryl intermediates of the enzymes, which subsequently oxidize the mediator or the substrate.…”
Section: Cmentioning
confidence: 99%
“…In contrast to the other three classes of heme peroxidases described above, DyP-type peroxidases are not members of the classical plant/microbial peroxidase superfamily, due to differences in sequence, structure and function [66,67]. Therefore, they represent an additional superfamily of heme-containing peroxidases.…”
Section: +mentioning
confidence: 96%